Reversal to Normal Anatomy (With Sleeve Gastrectomy) for Severe Hypoglycemia. (October 2021) - Vilallonga, Ramon; Rodríguez-Luna, María Rita; Roriz-Silva, Renato; Caubet, Enric; Gonzalez, Oscar; Ruiz de Gordejuela, Amador; Ciudin, Andrea; Armengol, Manel; Fort, José Manuel
Background. Laparoscopic Roux-en-Y gastric bypass (GBP) is an essential bariatric surgical procedure which is globally performed because of the associated effective weight loss and resolution of metabolic comorbidities, such as diabetes and dyslipidemia. Although some complications may occur, hypoglycemia is a rare complication, which can lead to lethal consequences. We aimed to describe the technical aspects and surgical results after reversal to normal anatomy (RNA). Methods. We conducted a retrospective data analysis including 16 patients who underwent laparoscopic RNA from 2011 to 2018. All data were archived in a prospective database. Previous bariatric surgery and postoperative outcomes were analyzed. Results. Sixteen patients underwent RNA, most of them after GBP, and 15 patients required sleeve gastrectomy. Among them, 80% were women; 5 patients presented with postoperative complications, such as colitis with intra-abdominal collection (n = 1), gastric leak (n = 2) treated with an endoprosthesis, mesenteric venous thrombosis (n = 1), and intra-abdominal bleeding (n = 1). Mean length of hospital stay was 5.93 (3-30). All patients recovered from their initial condition although 3 patients presented with mild hypoglycemia during follow-up. Seven patients regained weight (43.75%), and another 4 developed gastroesophageal reflux disease (25%). Conclusions. These laparoscopic RNA results are acceptable, indicating a clinical improvement in the hypoglycemic syndrome in all patients.